SISTEM PEMERINTAHAN DESENTRALISASI: Studi atas Penyebab Keruntuhan Daulah 'Abbasiyah - Ruwiyah Zamzam; Sayyid Ahsan Alawi (Yayasan Haiah Nusratul Islam, 2024)
The Abbasid Caliphate was one of the powers of the Muslim Ummah. Its emergence after the non-Arab movement fought for equality with the Arabs which was not obtained during the leadership of the Umayyad Daulah. The advantages possessed by the 'Abbasid Daulah besides being symbolized as the golden age of Islam, it turned out that the cause of its collapse was the application of decentralization in running the government, by one of the caliphs of the 'Abbasid Daulah named al-Mutawakkil. This type of research is a literature study or known as Library Research, using a descriptive approach to the findings or references from primary data, relating to the leadership of the 'Abbasid Daulah and the history of Islamic civilization. The decentralized government system applied by al-Mutawakkil was the main cause of the collapse of the 'Abbasid Daulah, this application was due to one of the emergence of small dynasties that wanted to break away from the 'Abbasid Daulah. In addition, al-Mutawakkli's lifestyle was a major factor, namely living in luxury, squandering wealth and so on.